Contributions to ontology reasoning and modeling - Eberhart, Aaron (Kansas State University, 2024)
This dissertation comprises research in diverse areas related to both ontology reasoning and ontology modeling. While these two topics differ in certain important ways, fundamentally data representation and modeling is central to the development of common-sense and useful reasoning methods, and useful reasoning applications enhance and enrich semantic models with ontologies. The contributions to both topics in this document are approached separately from a unified perspective, where ontology modeling and reasoning do not merely exist as adjacent topics, but instead inform each other. The five internal chapters each correspond to unique and related publications that all orbit this core topic and are contextualized in the introduction with central themes, which are then re-examined in the conclusion.
Keywords: Ontologies; Reasoning; Modeling